Dharmavīra Gāndhī, athavā, Mahātmā Mohanadāsa Karmacanda Gāndhīkā jīvana caritra - Sampūrṇānanda, 1891-1969 (SAMP early 20th-century Indian books project, 1916)
Biography of Mahatma Gandhi, 1869-1948, Indian statesman.